Alkoxylation of camphene over silica-occluded tungstophosphoric acid - Caiado, M.
Silica-occluded tungstophosphoric acid (PW-S-sg) was used as an efficient, environmentally friendly heterogeneous catalyst for the liquid-phase alkoxylation of camphene into their more valuable alkyl isobornyl ether, which is used as perfume and cosmetic products, in the pharmaceutical industry, as well as in the food industry. The alkoxylation of camphene with C-1-C-4 alcohols (methanol, ethanol, 1-propanol, 2-propanol, 1-butanol and 2-butanol) to alkyl isobornyl ether was studied in the presence of PW-S-sg (4.2% w/w) at 60-80 degrees C. Different linear and branched alcohols are compared in relation to their activity for the alkoxylation of camphene. The catalytic activity decreased with the increase of number of carbon atoms in the chain alcohol, which can be explained due to the presence of sterical hindrance and diffusion limitations inside the porous system of the catalyst. High selectivity of PW-S-sg catalyst for the alkyl isobornyl ether was observed. The effect of various parameters, such as catalysts loading, initial concentration of camphene and temperature were studied to optimise the ethoxylation of camphene. The catalytic stability of PW-S-sg in the ethoxylation of camphene was studied by performing consecutive batch runs with the same catalyst sample at the same conditions. After the third run, the catalytic activity stabilized. The catalyst can be recovered and reused without significant leaching of PW. The catalytic activity of PW-S-sg was compared with the activity of tungstophosphoric acid immobilized on silica by impregnation method (PW-S-im). The activity of PW-S-sg is higher than that of PW-S-im catalyst. After reaction, the PW-S-im, sample lost 20% of its heteropolyacid. (C) 2012 Elsevier B.V. All rights reserved.